Global families - Karraker, Meg Wilkes (Contemporary family perspectives, 2013)
'Global Families' provides family scholars with a methodical introduction to the interdisciplinary field of globalization. It then examines the ways in which globalization impinges on families throughout the world in four major areas: demographic transitions, world-wide culture, international violence, and transnational employment.